Efektivitas Metode Teams Games Tournamet (TGT) Berbantuan Modul Terhadap Sikap Toleransi Siswa - Bernadeta Yulisa; Nerita Setiyaningtyas; Hartutik Hartutik; FR. Wuriningsih (Universitas Maritim AMNI Semarang, 2023)
This study aims to describe, build, and maintain an attitude of tolerance in the era of society 5.0. The character of tolerance is a fundamental need of a pluralistic society. Tolerance creates a sense of serenity, peace, harmony and prosperity in social life. Willingness to side by side keeps people away from conflict, social tension, hostility, and division. Adolescents need direction, stimulus, and an environment to grow and implement a tolerant character. This study used a quantitative experimental research method. The research population was class X SMA PL Don Bosko Semarang. The aims of the study were: 1) to measure the effectiveness of the TGT method in increasing students' tolerance, 2) to improve student learning achievement using the module-assisted TGT method, 3) to strengthen tolerance so that student learning outcomes increase. The results showed that: 1) the module-assisted TGT method was considered effective in increasing students' tolerance, 2) TGT treatment improved student achievement, 3) tolerance had a significant influence on student learning outcomes.